Suppression of vortex-induced vibration of a square cylinder via continuous twisting at moderate Reynolds numbers. Issue 177 (June 2018) - Wu, Chih-Hua; Ma, Shengwei; Kang, Chang-Wei; Arthur Lim, Teck-Bin; Jaiman, Rajeev Kumar; Weymouth, Gabriel; Tutty, Owen
Abstract: Vortex-induced vibration (VIV) of elastic structures with a square-shaped prismatic column exposed to flow has a significant impact on many aspects of structural design and stability. The main aim of the present numerical study is to investigate an alternative design of square column for minimizing the impact of VIV on the elastic structures. The numerical study is carried out at moderate Reynolds numbers (1000 ≤ Re ≤ 22000). For both stationary and freely vibrating square cylinders, a systematic validation of the numerical results is performed with the available experimental data. In particular, various turbulence models are explored to assess their effectiveness to capture the separated wake flow dynamics behind the square cylinder. The simulation results via k−ω SST-SAS (Scale Adaptive Simulation) model are found closer to the reported measurements for both stationary and vibrating cases. After establishing the validity of our numerical methodology, the VIV simulations of twisted square cylinders with different twisted angles are performed at the moderate Reynolds numbers. In comparison to the square cylinder counterpart, the results of the twisted square cylinder demonstrate good controlling effect on the VIV response at two oncoming flow directions (0° and 45°). The twisted surface of the cylinder causes the variation of separation or vortex shedding points as well as the frequency of vortex shedding, which in turn affect the distributions of hydrodynamic forces along the cylinder. The power spectral analysis of hydrodynamic forces of twisted square cylinder indicates that the twisted surface has a significant influence on the frequencies of both drag and lift forces. Finally, comparisons of the detailed flow patterns, the 3D vortex structures and the vortex-shedding modes between square and twisted cylinders are presented in detail. Highlights: Significant suppression of vortex-induced vibration is found via using the twisting surface on the vibrating cylinder. The amplitude, drag, and lift forces of the cylinder are effectively reduced by the influence of the twisted surface. Different turbulence models (RANS, URANS, hybrid RANS/LES, LES) are tested in the current works of a vibrating cylinder. Design of twisted column has potential applications for future designs of multi-columns semisubmersibles to overcome VIM.